Identification of additional rRNA fragments encoded by the Plasmodium falciparum 6 kb element. - Feagin, J E (1997)
Sequences similar to mitochondrial large and small subunit rRNAs are found as small scattered fragments on a tandemly reiterated 6 kb element in the human malaria parasite Plasmodium falciparum. The rDNA sequences previously identified include strongly conserved portions of rRNA, suggesting that fragmented rRNAs derived from them are able to associate into functional ribosomes. However, sequences corresponding to other expected rRNA regions were not found. We here report that 10 of the 13 previously described rDNA regions have abundant small transcripts. An additional 10 transcripts were found from regions not previously known to contain genes. Five of the latter have been identified as rRNA fragments, including those corresponding to the 5'end and 790 loop sequences of small subunit rRNA and the sarcin/ ricin loop of large subunit rRNA. Demonstration that most of the previously described rDNA regions have abundant transcripts and the identification of new transcripts with other portions of conventional rRNAs provide support for the hypothesis that these small transcripts comprise functional rRNAs.